26.1k views
5 votes
Jacki evaluated the expression below.

2 cubed (3 minus 1) + 4 (8 minus 12) = 2 cubed (2) + 4 (4) = 8 (2) + 16 = 16 + 16 = 32.

What was Jacki’s error?

Jacki evaluated the expression below. 2 cubed (3 minus 1) + 4 (8 minus 12) = 2 cubed-example-1
User Nivs
by
5.7k points

2 Answers

6 votes

Answer:

C Jack did not subtract 12 from 8 correctly

Explanation:


2^3(3-1)+4(8-12)=2^3(2)+4(-4)

it should be -4, not +4

User Nils Luxton
by
5.3k points
4 votes
Jackie didn’t subtract 12 from 8 right, I think
User Tsdexter
by
4.7k points